1994
DOI: 10.1042/bj3030391
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-receptor agonist peptides, in contrast to thrombin itself, are not full agonists for activation and signal transduction in human platelets in the absence of platelet-derived secondary mediators

Abstract: Synthetic thrombin receptor peptides (TRPs), comprising the first 6-14 amino acids of the new N-terminus tethered ligand of the thrombin receptor that is generated by thrombin's proteolytic activity, were reported to activate platelets equally with thrombin itself and are considered to be full agonists [Vu et al. (1991) Cell 64, 1057-1068]. Using aspirin plus ADP-scavengers or the ADP-receptor antagonist adenosine 5'-[alpha-thio]triphosphate to prevent the secondary effects of the potent agonists that are norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 61 publications
(47 reference statements)
5
40
1
1
Order By: Relevance
“…Several authors have suggested that TRAP is only a partial agonist because it induces less expression of activated GPIIb-IIIa, fails to induce platelet prothrombinase activity, and causes weaker responses in terms of Ca ϩϩ mobilization, arachidonate production, and serotonin release. 8,9,28,29 Our studies do not fully support these concepts. In our hands, concentrations of thrombin and TRAP that induced similar aggregation responses in washed platelets resulted in nearly equivalent levels of phosphorylation at tyrosine residues of proteins present in whole platelet lysates.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Several authors have suggested that TRAP is only a partial agonist because it induces less expression of activated GPIIb-IIIa, fails to induce platelet prothrombinase activity, and causes weaker responses in terms of Ca ϩϩ mobilization, arachidonate production, and serotonin release. 8,9,28,29 Our studies do not fully support these concepts. In our hands, concentrations of thrombin and TRAP that induced similar aggregation responses in washed platelets resulted in nearly equivalent levels of phosphorylation at tyrosine residues of proteins present in whole platelet lysates.…”
Section: Discussioncontrasting
confidence: 78%
“…TRAP is able to induce aggregation and secretion by similar mechanisms than thrombin, 4 it is also involved in inositol phosphatase metabolism, 6 in inhibition of adenylcyclase, 7 and in protein phosphorylation. 8 Although it is generally accepted that TRAP acting on PAR-1 has the ability to induce many of the cellular responses observed after thrombin activation, comparative studies show that TRAP seems to be less efficient to induce the whole sequence of responses caused by thrombin. 4,9 -13 Considering that thrombin has an additional receptor on GPIb␣, differential responses to both agonists should be expected.…”
mentioning
confidence: 99%
“…The recent finding that neither thrombin receptor directly couples to G i indicates that thrombin operates a G i -independent mechanism for platelet activation (22). However, it is also well known that the G i independence of thrombin-induced platelet response is correlated to the concentration of the agonist, as ADP scavengers are able to affect platelet activation by low, but not high, doses of thrombin (22,29). In this work we report that activation of Rap1B by 0.1 unit/ml thrombin is only minimally affected by preincubation with ADP scavengers apyrase or creatine phosphate-creatine phosphokinase.…”
Section: Discussionmentioning
confidence: 99%
“…Specific peptides reproducing the sequence of the new N terminus of activated thrombin receptors are potent and selective activators of PAR-1 and PAR-4 and have been shown to trigger all of the platelet responses elicited by thrombin (24,28). However, several findings indicate that, in contrast to thrombin, thrombin receptor-activating peptides are not full agonists for platelet activation and that the support of secreted ADP is necessary to achieve complete platelet response (29,30). For instance, maximal doses of PAR-1-activating peptide (TRAP-1) require secreted ADP to trigger irreversible platelet aggregation, whereas ADP scavengers inhibit platelet aggregation only at low, but not high, doses of thrombin (29,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation